Recombinant LH administration in subsequent cycle after "unexpected" poor response to recombinant FSH monotherapy. (November 2014) - Papaleo, Enrico; Vanni, Valeria Stella; Viganò, Paola; La Marca, Antonio; Pagliardini, Luca; Vitrano, Rossella; Zanirato, Mara; Marsiglio, Elena; Privitera, Laura; Candiani, Massimo
Abstract Poor ovarian response (POR) is most frequently linked to the condition known as diminished ovarian reserve, but it can also occur in the absence of pathological ovarian reserve tests ("unexpected" POR). Because possible explanations include theca cells function deficiency, our aim was to evaluate the effect of r-LH administration in "unexpected" poor responders. A retrospective, single-centre, cohort study was conducted on 65 patients with AMH >0.5 ng/ml and/or AFC >5 with POR in their first cycle. Patients underwent a second IVF cycle with same protocol (long- or antagonist) and same starting dose of r-FSH used in the first cycle, plus daily addiction of 150 IU of r-LH from day 1. Compared to the first cycle, r-LH addition in the second cycle determined an increase in number of oocytes retrieved (p < 0.001), number of metaphase II oocytes (p < 0.05), E2 levels at hCG triggering (p < 0.001) and number of embryos transferred (p = 0.002). A 15% clinical pregnancy rate was also observed in the second cycle. Our results suggest that patients with non-pathological ovarian reserve tests and previous "unexpected" POR seem to benefit from r-LH addition in subsequent cycles without the need to increase the r-FSH starting dose, possibly due to an underlying occult theca cells deficiency.